Development of Integrated Use of Environmentally Friendly Technologies for Solid Waste Disposal in the Turkestan Region - Batyrkhanova, Akmaral; Aitimbetova, Akbota; Isayeva, Razia; Tanabayeva, Gulzira (Journal of Environmental Accounting and Management, 2026)
The purpose of the study is to investigate the main methods of MSW management, their advantages and disadvantages, selection of the optimal complex of environmentally safe methods of waste processing for use in the Turkestan region. The research was conducted using general scientific methods of cognition, in particular, system analysis, synthesis, abstraction, deduction, generalization, concretization, and comparative legal method. Possible MSW management schemes were analyzed from the standpoint of efficiency and impact on the environment, the dynamics of the effectiveness of methods depending on various factors of influence were presented, and optimal and real-to-implement comprehensive measures were developed to reduce the negative effect of solid waste on the environment and public health, and to improve the overall environmental situation in the region. In addition, the possibilities of applying innovative management and technological measures to minimize the impact of harmful substances in the composition of municipal solid waste, based on the synergy of environmental safety and economic efficiency, with the introduction of modern systems for monitoring the state of environmental pollution, have been investigated. The research shows that the proposed waste management system could significantly increase the municipal solid waste recycling rate in the Turkestan region from 16% to over 40%. In addition, it could reduce the amount of waste sent to landfill by over 50,000 tons per year. The system includes innovative waste sorting and recycling technologies that are estimated to be 35-40% more efficient than traditional methods.